Going the distance [videorecording (DVD)] - Burstein, Nanette; Barrymore, Drew; Long, Justin, 1978-; Applegate, Christina, 1971-; Sudeikis, Jason; Livingston, Ron; Garner, Kelli, 1984- (New Line Home Video, 2010)
Erin's wry wit and unfiltered frankness charms newly single Garrett over beer, bar trivia and breakfast the next morning. Their chemistry sparks a full-fledged summer fling, but neither expects it to last once Erin heads home to San Francisco and Garrett stays behind for his job in New York City. But when six weeks of romping through the city inadvertently become meaningful, neither is sure they want it to end.